The Meitei 'Maibis' (Shaman) of Manipur : a psychological perspective - Lourembam Roshan Singh (New Delhi Akansha Publishing House, 2020)
This book, rooted in the intellectual terrain of the interface of psychology and anthropology studies the personality profiles as well as the psychopathology of Meitei Maibis of Manipur who engage themselves in officiating as priestesses in the Lai Haraoba (god rejoicing) festival and other rites and rituals of the Meitei. Maibis play a vital role in Meitei society that comprises seven exogamous clans. Since the time immemorial, the Maibis have been working for the amelioration of mankind and its supernatural extension. Shamanism in Manipur as recorded in the oral tradition of people is believed to have been in existence since the time immemorial and has its own distinctive characteristics though it shares certain common features with the other forms of shamanism which are in vogue in different parts of the world. The book is to discuss the issues problems of Maibis possessing supernatural power and its relation to mental health. The relationship between socio demographic characteristics of the Meitei Maibis and their personality structure is highlighted in this book.
Includes bibliographical references (pages 202-215) and index.
Keywords: Meithei (South Asian people); Shamans; Meithei (South Asian people); Meithei (South Asian people); Shamanism; Manners and customs; Meithei (South Asian people)